2020
DOI: 10.1177/1523422320949143
|View full text |Cite
|
Sign up to set email alerts
|

Developing Employee Resilience: The Role of Leader-Facilitated Emotion Management

Abstract: The Problem To create resilient organizations, Human Resource Development (HRD) must foster the conditions (both internal and external to the employee) that enable learning and development in the face of adversity. Yet the experience of adversity produces intense negative emotions that threaten learning and development. Resilience building programs typically focus on building resources internal to the worker (e.g., self-efficacy, optimism) as a means of buffering against the negative effects of future stressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 75 publications
(170 reference statements)
2
27
0
Order By: Relevance
“…Positive emotions contribute to an upward spiral of social, physical, and psychological resources ( Fredrickson, 2001 ). These resources enable individuals to cope with adversity and “un-do” some of the impacts of negative emotions ( Richard, 2020 ), thereby facilitating their resilient growth ( Bunderson & Thompson, 2009 ; Malik & Garg, 2020 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Positive emotions contribute to an upward spiral of social, physical, and psychological resources ( Fredrickson, 2001 ). These resources enable individuals to cope with adversity and “un-do” some of the impacts of negative emotions ( Richard, 2020 ), thereby facilitating their resilient growth ( Bunderson & Thompson, 2009 ; Malik & Garg, 2020 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The individual may find advantages in such dysregulation, which enables them to avoid the effort involved in positive, proactive health regulation. Examples include self-handicapping strategies, procrastination in matters of health or other risky behaviors [ 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, prior studies have provided little insight into the precise affective mechanisms by which leaders motivate their followers (Yukl, 1998). Eberly and Fong (2013) found that leaders who express positive emotions are considered to be more effective by followers than those who express negative emotions (Richard, 2020). More of such investigations are encouraged, also in connection with how the other EI dimensions affect both leaders and their followers, including the role of "emotional contagion."…”
Section: Discussionmentioning
confidence: 99%
“…So far, prior studies have provided little insight into the precise affective mechanisms by which leaders motivate their followers (Yukl, 1998). Eberly and Fong (2013) found that leaders who express positive emotions are considered to be more effective by followers than those who express negative emotions (Richard, 2020). More of such investigations are encouraged, also in connection with how the other EI dimensions affect both leaders and their followers, including the role of “emotional contagion.” In addition to the SDT, it is likely that the social information processing theory can explain how followers process socio-emotional and related self-emotion-based information better from their job-based experiences, which they may use to “reframe” or “steer” levels of personal confidence and effort in performing their jobs.…”
Section: Discussionmentioning
confidence: 99%